Perintah khidmat masyarakat menurut kerangka syariah - Arifah Rahimah Ismail,; Mohd. Al Adib Samuri, (Universiti Kebangsaan Malaysia, 2014)
Western scholars consider community service order as the best alternative to rehabilitate offenders. However, Muslim jurists never debated the concept of community service order as a form of punishment in the Islamic judicial system. Accordingly, this article seeks to analyze the concept of community service order in the context of Islamic law by making a comparison between the concept of community service order as debated by Western scholars with the concept of ta`zir punishment by their Muslim counterpart. This aspect is analysed as an alternative concept of punishment, the discretionary power of judges, theory, or concept of the fundamental goals of punishment and penance. The research discovers that there are many similarities between the concept of community service order with the concept of punishment in Islamic ta`zir. This research is significant as it potrays that the implementation of community service order practised today is a sentence that is consistent with Islamic law.